FINANCIAL PERFORMANCE UNDER SHARIA CONSTRAINTS: THE ROLE OF GOVERNANCE AND SUSTAINABILITY IN ENERGY FIRMS - Achmad Soediro; Renisya Kusnadi; Ahmad Ridzki Pratama (Faculty of Economics and Business University of Mataram, 2026)
This study investigated how capital structure, green accounting, and Islamic Corporate Governance (ICG) influenced the financial performance of Sharia-compliant energy firms, with Corporate Social Responsibility (CSR) disclosure acting as a moderating mechanism. This research addressed the limited empirical integration of financial, environmental, and governance dimensions within Sharia-based performance frameworks, particularly in emerging markets. Grounded in Islamic Worldview and Sharia Enterprise Theory, this study conceptualized financial performance as a multidimensional outcome shaped by ethical governance and sustainability accountability. Using secondary data from 19 firms listed on the Indonesian Sharia Stock Index (ISSI) from 2020–2024, moderated regression analysis revealed that capital structure efficiency, green accounting practices, and ICG significantly enhanced the financial performance. The CSR disclosure further strengthened these relationships by reinforcing transparency and stakeholder trust. These findings extend Sharia Enterprise Theory by demonstrating how sustainability disclosure operationalizes Islamic accountability into measurable financial outcomes. The study offers an integrated empirical framework linking Islamic governance, sustainability practices, and firm performance, providing implications for regulators and managers seeking to strengthen the Sharia-compliant sustainability governance.